Darker, cooler, wetter: forest understories influence surface fuel moisture - Pickering, Bianca J; Duff, Thomas J; Baillie, Craig; Cawson, Jane G (Agricultural and forest meteorology, 2021)
•Understorey vegetation alters near-surface microclimate and surface fuel moisture•Dense understorey forest was cooler and more humid at the near-surface•Screen height microclimate measurements could underpredict of fuel moisture•The effects of the understorey should be considered when estimating fuel moisture The moisture content of dead leaves, twigs and bark on the forest floor is a key determinant of fire behaviour. The microclimate inside forests, which drive the moisture content of these dead fuel components, is typically measured at screen height (150 cm). However, in some forest types, the surface fuel at ground level may be subject to additional sheltering from low shrubs, ferns and grasses, which could alter the microclimate near the surface (hereafter near-surface). In such cases, screen height measurements may not adequately represent the near-surface conditions that determine dead fuel moisture contents. We sought to quantify the effect of understorey vegetation on near-surface microclimate. We measured in-forest temperature, relative humidity and solar radiation in eucalypt forests over two fire seasons at both screen height and the near-surface using weather stations at 25 sites. The sites encompassed wet eucalypt forest (n=18) with a dense, mesic understorey and dry eucalypt forest (n=7) with a sparser, scleromorphic understorey. Wet forests with dense understorey vegetation had near-surface air temperatures that averaged 1.3°C lower, relative humidities that averaged 13.1% higher and total solar radiation that was 0.84 MJ less per day compared with those measured at screen height. These microclimate differences led to predicted fuel moistures which averaged 4.7% higher at the near-surface compared with screen height – this was statistically significant. In contrast, dry forests with less understorey vegetation, had near-surface air temperatures that averaged 4.2°C higher, and relative humidities that averaged 3.1% lower compared to screen height. These differences were not large enough to translate into statistically significant differences in predicted fine fuel moisture between heights. Overall, these findings show that understorey vegetation plays an important role in moderating near-surface microclimate in some forest types and this needs to be taken into consideration when predicting fuel moisture.